Aryne-Mediated Arylation of Hantzsch Esters: Access to Highly Substituted Aryl-dihydropyridines, Aryl-tetrahydropyridines and Spiro[benzocyclobutene-1,1′-(3′,4′-dihydropyridines)] - Sun, Weitao; Trinchera, Piera; Kurdi, Nada; Palomas, David; Crespo-Otero, Rachel; Afshinjavid, Saeed; Javid, Farideh; Jones, Christopher R. (Synthesis, 2018)
This is a full account of our studies into the generation of highly functionalised 2-aryl-1,2-dihydropyridines and 2-methylene-3-aryl-1,2,3,4-tetrahydropyridines via intermolecular aryne ene reactions of Hantzsch esters. Furthermore, exposure to excess aryne revealed unusual 3′-aryl-spiro[benzocyclobutene-1,1′-(3′,4′-dihydropyridines)]. Mechanistic insights are provided by deuterium-labelling studies and DFT calculations, whilst preliminary cytotoxicity investigations reveal that the spirocycles are selective against colon carcinomas over ovarian cancer cell lines and that all the compounds have high selectivity indices with regards to non-cancer cells.
Keywords: arynes; ene reaction; spiro compounds; benzyne; Hantzsch esters; dihydropyridines